Navigating Conflicts Related to Religious and Non-Religious Identity on Campus. Issue 3 (2nd July 2016) - Patel, Eboo; Montero, Janina; Love, Cindi; Giess, Mary Ellen
Abstract: Matters of interreligious engagement and worldview orientation are becoming more salient on campuses across the country. All-comers policies, conflicts about the Middle East, and intersections of spirituality with other aspects of identity present challenges for professionals working with students on college campuses. This article will discuss some of the intricacies to addressing conflict around religious identity on campus, focusing on the importance of building relationships across disagreement.